Sustainable local economic development indicator framework: A tool for property building redevelopment projects. Issue 5 (19th October 2020) - Wilson, Darrin; Polter, Rosalia
ABSTRACT: Sustainable Local Economic Development has been an emerging approach to economic development for more than a decade, with the goal of enhancing economic, social, and environmental sustainability. As practitioners seek and implement sustainable economic development projects, an indicator framework is needed to ensure these projects are contributing to the sustainability of the community. The purpose of this paper is to propose an indicator framework using the five principles of Sustainable Local Economic Development (SLED). Specifically, the indicator framework is designed to score historic property redevelopments that utilize Historic Tax Credits. These projects have become more prevalent in community/economic development as they provide communities an opportunity to reactivate or enhance physical assets for the purpose of development. The goal of the indicator framework is to provide practitioners the ability to analyze data related to the historic property redevelopment project and determine how well the project meets the five principles of SLED.